Interdisciplinarity and Local Knowledge to Foster Community Resilience in Disaster Risk Management: A Community-Based Educational Approach on the Chilean Coast - Jofre-Leiva, D (Elsevier Ltd, 2025)
This article explores the transformative potential of community-based disaster risk management (DRM) schools by emphasizing the critical role of comprehensive, participatory, and inclusive approaches in resilience building. Using the Environmental Community School of the Coast (ECAC) in Cartagena, Chile, as a case study, it demonstrates how integrating local and scientific knowledge through interdisciplinary collaboration fosters socio-environmental governance and community resilience. This approach aligns with international frameworks advocating for multistakeholder participation, communication, education, and shared responsibilities across sectors. Developed through participatory action research and co-creation with local communities, the ECAC illustrates how interdisciplinary efforts can address socio-environmental challenges and shape disaster risk reduction (DRR) strategies. The article discusses the theoretical and practical contributions of the ECAC, highlighting its innovative educational model, the challenges of interdisciplinary work, and the importance of social learning and local engagement. Findings underscore the necessity of addressing social vulnerabilities through community-based education programs, which enhance resilience by preserving traditional knowledge, fostering community cohesion, and empowering local decision-making. This research contributes to the literature on DRM and community resilience by presenting a replicable framework for inclusive disaster governance and transformative learning. It reflects on academia s evolving role in fostering interdisciplinary and transdisciplinary collaboration, offering evidence-based insights into the success factors and challenges of creating community schools capable of enhancing territorial resilience and socio-environmental governance. © 2025 Elsevier Ltd